Breakthrough in Xenon Capture and Purification Using Adsorbent‐Supported Silver Nanoparticles. Issue 28 (1st June 2016) - Deliere, Ludovic; Coasne, Benoit; Topin, Sylvain; Gréau, Claire; Moulin, Christophe; Farrusseng, David
Abstract: Rare gas capture and purification is a major challenge for energy, environment, and health applications. Of utmost importance for the nuclear industry, novel separation processes for Xe are urgently needed for spent nuclear fuel reprocessing and nuclear activity monitoring. The recovered, non‐radioactive Xe is also of high economic value for lighting, surgical anesthetic, etc. Here, using adsorption and breakthrough experiments and statistical mechanics molecular simulation, we show the outstanding performance of zeolite‐supported silver nanoparticles to capture/separate Xe at low concentrations (0.087–100 ppm). We also establish the efficiency of temperature swing adsorption based on such adsorbents for Xe separation from Kr/Xe mixtures and air streams corresponding to off‐gases generated by nuclear reprocessing. This study paves the way for the development of novel, cost‐efficient technologies relying on the large selectivity/capacity of adsorbent‐supported silver nanoparticles which surpass all materials ever tested. Abstract : Xenon capture : Zeolite‐supported silver nanoparticles exhibit very large selectivity for xenon separation from krypton/xenon mixtures as well as from air streams. Such adsorbents loaded with small polarizable nanoparticles (opened metallic surfaces) combine high adsorption capacity and selectivity which allows envisioning the design of novel, cost‐efficient processes to separate and capture Xe (see figure).